Principles of Development - Wolpert, Lewis (Oxford University Press, 2002)
Written by a team of distinguished authors, this text focuses on principles and key concepts to guide students through this challenging subject. Those universal principles governing development in vertebrates, invertebrates, and plants are explained, through both words and pictures.